Drug therapy and medication adherence in type 2 diabetes in a care facility: A cross sectional survey - Uchenna I.H. Eze; Tolulope F. Akhumi; Chinonyerem O. Iheanacho; Sule A. Saka (Elsevier, 2022)
Background: Adherence to medications improves glycaemic control and reduces diabetes-related morbidity and mortality. Objectives: The study assessed drug therapy for type 2 diabetes, glycaemic control and association of medication adherence with socio-demographic and clinical data, among adult diabetic patients attending a healthcare facility. Methods: Cross-sectional survey and hospital records were used to obtain data. The study included 200 adults with type 2 diabetes mellitus in a Nigerian healthcare facility. Data on patients clinical characteristics, diabetes drug therapy and medication adherence were collected, entered and anlaysed using SPSS version 24 (P < 0.05). Primary outcome measure was medication adherence among the patients, while secondary outcome measures was glycaemic control. Results: A total of 200 (100%) respondents participated in the study and the majority 141(70.5%) were over 60 years old. Oral medications were mostly used 187(93.5%), particularly, metformin 199(99.5%) and pioglitazone 100(50.0%), while dipeptidyl peptidase-4 inhibitors were not used at all. Patients mostly had poor glycaemic control 159 (79.5%) and majority 152(76.0%) did not practice self-blood glucose monitoring. Moderate medication adherence was predominant in the population. Class of medicine and socio-demographics were not significantly associated with medication adherence (P > 0.05), unlike results of blood glucose self-tests (p = 0.001). Conclusion: Oral antidiabetics, particularly metformin and pioglitazone were mostly used. Poor glycaemic control and moderate adherence were found in the patients, and medication adherence was associated with self-glucose monitoring. This emphasises the need for regular diabetes education on medication adherence.